Laporan Kasus: Menangani Penyakit Ginjal Kronis pada Anjing Peranakan Pomeranian - Pradnyani, Gusti Ayu Putu Indira; Widiastuti, Sri Kayati; Erawan, I Gusti Made Krisna (Indonesia Medicus Veterinus; Vol 10 (3) 2021, 2021)
Chronic kidney disease (CKD) is a progressive and irreversible disorder of kidney function. A Pomeranian Mix dog named Kitty, 10 years old, has a female sex examined at the Sunset Vet Bali Animal Clinic.The case dog has a history of heart problems and liver disorders. The case dog returns to the clinic suspected of having kidney problems. The case dog had polyuria, vomiting, anorexia, diarrhea and lethargy. The case dog also lost weight every month. On physical examination, the Body Condition Score (BCS) was 5/9, breath rate 60x / minute, heart rate 150x / minute (tachycardia), auscultation of a heart sound murmurs. Routine haematological examination showed the case dog had polycythemia and had erythrocyte morphological abnormalities, namely a low MCV value (microcytic). On serum biochemical examination, there was an increase in BUN, creatinine, phosphate, globulin levels and decreased levels of calcium and sodium. In the urine specific gravity examination, the results obtained were 1,015 and the SDMA test obtained result 15 ?g / dL. Therapy with diet, fluid therapy, maropitant, furosemide, ipakitine powder, enalapril and calcium gluconate. Evaluation on the 5th day of inpatient and treatment of case dogs showed a better condition, based on several clinical signs observed, namely the absence of vomiting, stable breathing patterns, the case dog began to be responsive and there was no diarrhea. On the 10th day, several parameters of blood biochemical serum including examination of BUN levels which decreased from the initial examination, while the levels of creatinine, phosphate and calcium were in the normal range.